ChemInform Abstract: Asymmetric Total Synthesis of Apocynaceae Hydrocarbazole Alkaloids (+)‐Deethylibophyllidine and (+)‐Limaspermidine. Issue 37 (September 2015) - Du, Ji‐Yuan; Zeng, Chao; Han, Xiao‐Jie; Qu, Hu; Zhao, Xian‐He; An, Xian‐Tao; Fan, Chun‐An
Abstract An unprecedented asymmetric tandem aminolysis/aza‐Michael addition reaction of spirocyclic para‐dienoneimides [e.g. (I)] with the formation of the chiral quaternary center in the densely functionalized hydrocarbazole synthons [e.g. (III)] is studied.